2015
DOI: 10.15420/aer.2015.04.02.122
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Cardiac Resynchronisation Therapy

Abstract: Since the introduction of CRT more than 20 years ago, its role in mild to severe systolic heart failure has become well established.CRT has been shown to decrease mortality, reduce heart failure hospitalisations and improve functional status in patients with NYHA class II-IV heart failure and QRS prolongation, most commonly with LBBB pattern.1 One of the major limitations of CRT implementation is the significant number of 'appropriate' candidates, as determined by guidelines, who fail to respond with clinical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(63 reference statements)
0
5
0
1
Order By: Relevance
“… 9 Overall, an unfavorable CS anatomy precludes the delivery of an LV lead placement in 5%–8% of patients, and the lead position is suboptimal in another 15%–20% of patients. 10 In a contemporary meta-analysis of 29,503 patients, the overall rate of failure of implantation of an LV lead was 3.6% (95% confidence interval [CI], 3.1%–4.3%). The rate of failure in studies that commenced before 2005 was 5.4% (95% CI, 4.4%–6.5%), and that in studies performed from 2005 onward was 2.4% (95% CI, 1.9%–3.1%; P < .001).…”
Section: Discussionmentioning
confidence: 99%
“… 9 Overall, an unfavorable CS anatomy precludes the delivery of an LV lead placement in 5%–8% of patients, and the lead position is suboptimal in another 15%–20% of patients. 10 In a contemporary meta-analysis of 29,503 patients, the overall rate of failure of implantation of an LV lead was 3.6% (95% confidence interval [CI], 3.1%–4.3%). The rate of failure in studies that commenced before 2005 was 5.4% (95% CI, 4.4%–6.5%), and that in studies performed from 2005 onward was 2.4% (95% CI, 1.9%–3.1%; P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Small trials have suggested that CRT non-responders might benefit from placement of an additional LV lead to achieve multisite LV pacing 28. Lenarczyk et al showed that triple-site CRT is more beneficial than conventional CRT and upgrade to triple-site CRT should be considered in non-responders to standard resynchronisation 29.…”
Section: Introductionmentioning
confidence: 99%
“…The only alternative to transvenous CS cannulation has been surgical placement of epicardial LV leads, an approach with significantly increased risk due to the invasive nature of the procedure 28. The data regarding epicardial/surgical LV lead placement are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines from the American College of Cardiology/American Heart Association/Heart Rhythm Society recommend CRT for HF patients with a functional class III or IV, left ventricle ejection fraction (LVEF) < 35%, and an electrocardiogram trace with a QRS complex greater than 120 milliseconds [ 14 , 15 ]. Efficacy of CRT has been demonstrated in multiple trials, showing a significant improvement in 6-minute walk distance, quality of life, peak oxygen uptake, functional classification, hospital admissions, and mortality among patients with left ventricle (LV) malfunction, and ventricular electric conduction disorders [ 16 , 17 ]. The improvement in LVEF seems to correlate with a better long-term survival [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them use cine myocardial tagging and strain imaging, a technique that presents a tridimensional map that changes in color reflecting the timing and distribution of circumferential strains during mechanical contraction and relaxation. In a patient with ventricular contraction abnormality, the map will show heterogeneity in color coding mainly related to the septum and the lateral wall [ 16 ]. Nevertheless, the time processing to achieve this map is too high and it might suffer from meaningful degradation.…”
Section: Introductionmentioning
confidence: 99%